KAPASITAS ADAPTIF EKOLOGIS GUGUS PULAU GURAICI KECAMATAN KAYOA, KABUPATEN HALMAHERA SELATAN, PROVINSI MALUKU UTARA (Ecological Adaptive Capacity of Guraici Islands Group Sub-District Kayoa, Southern Halmahera District, North Moluccas Province) - Riyadi Subur; Fredinan Yulianda; Achmad Fahrudin; Setyo B. Susilo (Bogor Agricultural University, 2013)
ABSTRACTCoral reef, mangrove, and seagrass bed are important ecosystems in coastal areas and small islands which plays critical roles in maintenance of shorelines and lands on small islands. Those ecosystems have mutual relationships in providing effective protection of lands and lives on small islands. The objectives of the research are to calculate, to valuate, and to determine ecological adaptive capacity small islands of Guraici Islands. Field work was carried out at all 17 islands of Guraici Islands, where data collection and calculations of each ecosystem adaptive capacity of coral reef, mangrove and seagrass bed were made. Values of adaptive capacity for each ecosystem are found to range between 0.0 and 1.0 whereas values of the ecological adaptive capacity of every single island in Guraici Islands range between 0.0 and 3.0. The results of this research indicate that all small island ecosystems studied in Guraici Islands can be grouped into three categories of adaptive capacity, they are â€œmedium, low, and very lowâ€. Values of coral reefs adaptive capacity range between 0.0 and 0.58. Values of mangroves adaptive capacity range between 0.0 and 0.51. Values of seagrass beds adaptive capacity range between 0.0 and 0.51. Data analysis made also shows that small island ecological adaptive capacity in Guraici Islands has also belonged to three categories â€œmedium, low, and very lowâ€, where all their adaptive capacity values range between 0.37 and 1.64. Ten islands are in â€œMediumâ€ category, six islands in â€œlowâ€ category, and one island is in â€œvery lowâ€ category.Key words: coral reef, ecological adaptive capacity, mangrove, seagrass——-ABSTRAKTerumbu karang (coral reef), mangrove dan padang lamun (seagrass bed), merupakan ekosistem penting di wilayah pesisir dan pulau-pulau kecil yang memegang peranan penting dalam melindungi garis pantai serta daratan pulau kecil. Ekosistem tersebut cukup efektif sebagai pelindung terhadap keselamatan lahan daratan pulau-pulau kecil, dan memiliki keterkaitan dalam melindungi pulau-pulau kecil. Tujuan peneliltian ini adalah menghitung, menilai serta menentukan status kapasitas adaptif ekologi pulau-pulau kecil dalam Gugus Pulau Guraici. Penelitian dilakukan pada 17 pulau yang terdapat dalam Gugus Pulau Guraici, dengan menghitung kapasitas adaptif ekosistem terumbu karang, ekosistem mangrove dan ekosistem lamun. Nilai Kapastias adaptif setiap ekosistem tersebut berkisar 0,0-1,0, sedangkan nilai kapasitas adaptif ekologi pulau berkisar 0,0-3,0. Hasil penelitian ini menunjukkan bahwa seluruh ekosistem pesisir yang diteliti pada pulau-pulau dalam Gugus Pulau Guraici tergolong dalam tiga kategori kapasitas adaptif yaitu â€œsedang, rendah dan sangat rendahâ€. Nilai kapasitas adaptif ekosistem terumbu karang berkisar 0,0-0,58.Ekosistem mangrove memiliki nilai kapasitas adaptif berkisar 0,0-0,51, dan ekosistem lamun kapasitas adaptifnya berkisar 0,0-0,59. Hasil analisis juga menunjukkan bahwa kapasitas adaptif ekologi pulau-pulau dalam Gugus Pulau Guraici tergolong kedalam tiga kategori yaitu â€œsedang, rendah dan sangat rendahâ€, dengan nilai kapasitas adaptif ekologi yang berkisar 0,37-1,64. Sebanyak sepuluh pulau tergolong memiliki kapasitas adaptif ekologi â€œsedangâ€™, enam pulau memiliki kapasitas adaptif ekologi berkategori â€œrendahâ€, dan satu pulau berkategori kapasitas adaptif ekologi â€œsangat rendahâ€.Kata kunci: terumbu karang, kapasitas adaptif ekologis, mangrove, lamun